Analysis of The Acceleration of Time and Cost of Implementing Building Construction Projects Using The Critical Path Method (CPM) Method - Nur Yaqin, Heru; Teki Tjendani, Hanie; Witjaksana , Budi (Devotion : Journal of Research and Community Service, 2023)
This study aims to obtain the form of project work network in the Probolinggo City Hospital Development Project, to determine the effect of accelerating the duration of Probolinggo City Hospital Development work on network planning and to find out the amount of costs incurred before and after the acceleration of the duration of project work. The method used is the acceleration method with modification of the scheduling of the CPM model. CPM method planning is a recommendation in choosing from many existing methods, because there is a calculation of the earliest time the project starts, the last time the project starts as well as the earliest time to finish and the last time to finish so that it can be known the time lag of all activities. Data Used are primary and secondary data related to the sequence and relationship of activities, implementation time and cost budget plan (RAB). In this thesis, the author takes scheduling data from the Probolinggo City Hospital Development Project which will be used as the basis for writing this thesis in conducting CPM analysis and accelerating the duration of work with additional overtime working hours and calculating the total cost of the acceleration to be used as comparison material in the writing results. Based on the analysis that has been carried out using the Microsoft Project 2016 application, the normal duration of structural work is 81 working days and has 18 critical units of 31 work items. After the acceleration was carried out, there was a decrease in the duration of the work of the structure to 74 working days. The difference in duration decrease was 7 days or 9.45%. The total initial cost with the normal duration for structural work is IDR 28,563,131,560, while after acceleration, the project cost for structural work becomes IDR 28,635,083,793